FINANCIAL INCLUSION IN RURAL INDIA: A BANK GROUP WISE ANALYSIS - Sharma, Ruchi (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The study aims to construct a financial inclusion index for rural areas to make a bank group-wise comparative analysis of rural financial inclusion. The data is taken at four data points: 2005, 2010, 2015, and 2019. The scope of the study is confined to scheduled commercial banks. The construction of financial inclusion index is based on three fundamental elements of banking penetration, accessibility of banking services, and utilisation of the banking system. The proposed IFI spans from 0 to 1, where zero denotes the minimal degree of financial inclusion and one indicates complete financial inclusion.